2011
DOI: 10.1586/era.11.95
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative irradiation in extremity soft tissue sarcoma

Abstract: Adjuvant radiotherapy constitutes an important component of the treatment of soft tissue sarcomas. Extremity soft tissue sarcomas constitute a large proportion of this rare mesenchymal tumor. Questions regarding timing, techniques and toxicity come into play about optimizing adjuvant radiotherapy. This article will discuss recent trends and outcomes of perioperative, that is, preoperative and postoperative, irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 82 publications
0
1
0
Order By: Relevance
“…In humans, some bone sarcomas, most commonly Ewing sarcoma, adjuvant radiotherapy is a treatment option, being reported adverse effects of radiation therapy on up to 74% of patients [76][77][78], namely wound healing problems, infection, muscle and joint contracture, ankylosis, osteitis, non-union, pathological fractures, tendon adhesion, and radiation induced sarcoma [76][77][78][79]. In a rabbit tibia model, it was demonstrated that radiation exposure decreases the quantity and quality of regenerate and angiogenesis during a DO [80].…”
Section: Distraction Osteogenesis After Oncologic Surgerymentioning
confidence: 99%
“…In humans, some bone sarcomas, most commonly Ewing sarcoma, adjuvant radiotherapy is a treatment option, being reported adverse effects of radiation therapy on up to 74% of patients [76][77][78], namely wound healing problems, infection, muscle and joint contracture, ankylosis, osteitis, non-union, pathological fractures, tendon adhesion, and radiation induced sarcoma [76][77][78][79]. In a rabbit tibia model, it was demonstrated that radiation exposure decreases the quantity and quality of regenerate and angiogenesis during a DO [80].…”
Section: Distraction Osteogenesis After Oncologic Surgerymentioning
confidence: 99%